The Path of Peace as a Conflict Resolution of Ordinary Crimes in Criminology Perspective in Indonesia - Budianto, Agus (International Journal of Criminology and Sociology, 2022)
A peaceful path as a conflict resolution against general criminal acts can be realized in the provisions of criminal reform in the 2014 RKUHP in Indonesia. however, this RKUHP has come into conflict with the public over several crucial articles, so that the President of Indonesia said to cancel the application in 2019. As a result, several general criminal offences are still being processed in the Criminal Justice System. This paper is the result of a juridical the sociological study, with the main data being primary in the form of interviews with several informants with non-random sampling technique and using a case approach and deductive analysis. The results showed that the use of imprisonment on defendants of criminal offences to provide a deterrent effect was wrong. The application of imprisonment does not change the convict for the better, coupled with the fact that prisons in Indonesia are entering an extreme overcrowding situation which then the density has an impact on the coaching program in Lapas not going well. One strategy to overcome these problems is by efforts to form and develop the concept of restorative justice.